Understanding human-fire interactions in tropical forest regions: a case for interdisciplinary research across the natural and social sciences - Carmenta, R.; Parry, L.; Blackburn, A.; Vermeulen, Sonja J.; Barlow, J. (2011)
Fire in the forested tropics has profound environmental, economic, and social impacts at multiple geographical scales. Causes of tropical fires are widely documented, although research contributions are from many disciplines, and each tends to focus on specific facets of a research problem, which might limit understanding of fire as a complex social-ecological system. We conducted a systematic review to (1) examine geographic and methodological focus in tropical fire research; (2) identify which types of landholders are the focus of the research effort; (3) test for a research method effect on the variables, e.g., socio-political, economic, and climatic, identified as causes of and proposed management solutions to tropical fire; and (4) examine relationships between causal factors and proposed solutions. Results from 51 studies show distinct geographic and methodological tendencies in the literature. Few studies explicitly identify landholder types, and no social studies focused on large-landholders. Multiple drivers and potential solutions to preventing fire are identified and the research approach adopted had the strongest influence on the socioeconomic, direct fire management and landscape characteristics variables. There was an overall mismatch between identified cause and proposed management solution. These findings indicate that mixed method approaches are imperative to understanding the coupled human-nature system of fire and to improve rural development and management strategies to curtail tropical fire spread.